Model Sekolah Ramah Ham (Sr-Ham) sebagai Solusi Terhadap Pelanggaran Hak Asasi Manusia di Sekolah - Athira Salsa Rahmi; Dwigia Mardia Dalpen; Adrias Adrias; Fadila Suciana (International Forum of Researchers and Lecturers, 2025)
This research aims to analyze literature related to solutions for dealing with Human Rights (HAM) violations in the school environment through the implementation of the Human Rights Friendly School (SR-HAM) model. The method used in writing this article is literature study. A Human Rights Friendly School is a school concept that integrates human rights values ​​as a core principle in school management and organization, where human rights values ​​are at the center of the learning process and student experience and are present in all aspects of school life. The SR-HAM concept approach combined with Ki Hadjar Dewantara's educational concept is expected to be able to provide effective solutions in dealing with various human rights problems in schools. Although the concept of Human Rights Friendly Schools initiated by Amnesty International and Ki Hadjar Dewantara conceptually supports the achievement of national education goals, its implementation needs to be carried out correctly and appropriately in order to provide the best results.